2015
DOI: 10.1007/s12032-015-0633-8
|View full text |Cite
|
Sign up to set email alerts
|

The c-Myc–LDHA axis positively regulates aerobic glycolysis and promotes tumor progression in pancreatic cancer

Abstract: The transcription factor c-Myc plays critical roles in cancer development and progression through regulating expression of targeted genes. Lactate dehydrogenase A (LDHA), which catalyzes the conversion of l-lactate to pyruvate in the final step of anaerobic glycolysis, is frequently upregulated in pancreatic cancer. However, little is known about the effects of c-Myc–LDHA axis in the progression of pancreatic cancer. In this study, we found that c-Myc and LDHA are concomitantly overexpressed in pancreatic canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 22 publications
2
68
0
Order By: Relevance
“…None of these frequently mutated genes individually defines a clear subtype, although some, like CDKN2A, SMAD4, or MYC, have been shown to have a prognostic impact [22][23][24]. It appears that some mutations may be more frequent within one histological variant, such as MYC amplification in adenosquamous carcinomas, but this remains to be demonstrated in large series [25].…”
Section: Genomic Pdac Subtypesmentioning
confidence: 99%
“…None of these frequently mutated genes individually defines a clear subtype, although some, like CDKN2A, SMAD4, or MYC, have been shown to have a prognostic impact [22][23][24]. It appears that some mutations may be more frequent within one histological variant, such as MYC amplification in adenosquamous carcinomas, but this remains to be demonstrated in large series [25].…”
Section: Genomic Pdac Subtypesmentioning
confidence: 99%
“…c-Myc upregulates transcription of PTB, hnRNPA1, and hnRNPA2, ensuring a high PKM2/PKM1 ratio. LDHA was identified as another c-Myc responsive gene [126, 127]. Knockdown of c-Myc reduces the expression of LDHA, lactate production, and glucose consumption [127].…”
Section: Regulation Of Glycolysis In Tumorsmentioning
confidence: 99%
“…LDHA was identified as another c-Myc responsive gene [126, 127]. Knockdown of c-Myc reduces the expression of LDHA, lactate production, and glucose consumption [127]. LDHA overexpression is required for c-Myc-mediated transformation and tumor growth [126, 127].…”
Section: Regulation Of Glycolysis In Tumorsmentioning
confidence: 99%
“…Lactate dehydrogenase A (LDHA) catalyzes the final step of glycolysis in which pyruvate is directly converted to lactate, indicating the critical role for maintaining glycolysis in tumorigenesis [14] . It has been reported that the expression of LDHA is abnormal in many human cancers, such as prostate cancer [15] , ovarian cancer [16] , pancreatic cancer [17,18] and breast cancer [19] . Meanwhile, inhibition of LDHA reduced several tumor progression [14][15][16][17] , indicating the underlying role of LDHA as a promising target for cancer therapy.…”
mentioning
confidence: 99%
“…In prostate cancer, inhibition of LDHA suppresses tumor progression and growth [15] . In pancreatic cancer, reduced c-myc-LDHA signaling resulted in decreased tumor growth and metastasis [18] . In clear cell RCC, previous studies showed that the expression of LDHA is upregulated compared to normal renal tissue [20] , and furthermore, many studies have the view that targeting the glucose metabolism may represent an interesting tool to improve the efficacy of specific immunotherapeutic approaches [2,21] .…”
mentioning
confidence: 99%